DAMPAK STRESS PADA ORANG TUA YANG MENGASUH ANAK BERKEBUTUHAN KHUSUS - Rr. Aliifah Maurizka Ghaisani; Wiwin Hendriani (Institut Pendidikan Tapanuli Selatan, 2022)
Being part of the family of children with special needs certainly has its own challenges because they have to face and live a different life from other families in general. The purpose of this literature study is to reveal the impact of stress on parents who have children with special needs, especially in their daily lives. The journals used for the study of literature in this study were taken from 2 journal databases, namely Science Direct, and Google Scholar with a limited publication year of 2011-2021. The initial search found 32 journals which were then selected by applying inclusion and exclusion criteria so that 3 journals (N=3) were obtained, namely 2 quantitative journals and 1 mixed method journal. Based on the reviews obtained, the impact of stress on parents is very diverse, considering that the journal sources used are not fixed on one type of disability in children. There are parents who are classified as mild stress which has an impact on their daily lives such as displaying excessive work spirit behavior, easily tired, and unable to relax. Meanwhile, parents who have excessive worries about their children will have an impact such as being overprotective or limiting social interaction with the surrounding environment. As well as the stress of parenting who depend on relying on their partner to meet the demands of parenting, because they are no longer able to cope on their own. By knowing what the impact of stress experienced by parents who care for children with special needs will be the basis in the preparation of effective parenting programs in coping with stress due to caring for children with special needs.